Analisis Pengaruh Atribut Produk, Celebrity Endorser Dan Perceive Value Sebagai Variabel Intervening Terhadap Keputusan Pembelian Produk Handbody Nivea Di Kota Semarang - Astri Dita Kumalasari (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
Research on the influence of product attributes, celebrity endorsers and perspective value on purchasing decisions for Nivea Handbody products in Semarang City. The expected aim of this research is to analyze the influence of product attributes on Perceive value, as well as to analyze the influence of Endorsers on Perceive value. With the population of all consumers who purchased Nivea Handbody Products, the exact number is not known, so the sampling technique used in this research is purposive sampling, namely a sample collection method based on research objectives with a total of 100 people. The data analysis technique used is Path linear regression analysis to analyze the influence of Product and Endorser Attributes on Purchase Intention with Perceive value as the intervening variable for the test tool used and adapted to the research model. The regression equation used is Model 1, namely the influence of Product Attributes and Endorsers on Perceive value. Model 2 is the influence of Product Attributes, Endorser and Perceive value on Purchase Intention. Based on the results of the research that has been carried out, it can be concluded that product attributes influence perceived value in a positive direction, meaning that if product attributes increase, then perceived value increases, Endorsers influence Perceive value in a positive direction, meaning that if endorsers increase, then Perceive value increases, Product attributes influence Purchase intention in a positive direction, meaning that if product attributes increase, then purchase intention increases, Endorsers influence Perceive value in a positive direction, meaning that if endorsers increase, then purchase intention increases, Perceive value influences Purchase intention in a positive direction, meaning that if Perceive value increases, Purchase intention increases. Perceive value has the most dominant influence on Purchase intention. Product and Endorser attributes have a direct influence on Purchase intention through Perceive value.